2020
DOI: 10.1038/s41467-020-18462-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical entrapment and killing of insects by bacteria

Abstract: Actinobacteria produce antibacterial and antifungal specialized metabolites. Many insects harbour actinobacteria on their bodies or in their nests and use these metabolites for protection. However, some actinobacteria produce metabolites that are toxic to insects and the evolutionary relevance of this toxicity is unknown. Here we explore chemical interactions between streptomycetes and the fruit fly Drosophila melanogaster. We find that many streptomycetes produce specialized metabolites that have potent larvi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…A recent report has also shown that newly mated queens of Solenopsis invicta (red imported fire ant) are attracted by geosmin and 2-MIB to Streptomyces -rich locations for nesting, which have reduced levels of pathogenic fungi [ 36 ]. In addition, 2-MIB attracts Drosophila melanogaster (common fruit fly) for oviposition, where other Streptomyces specialized metabolites, such as cosmomycin D and avermectin, kill the larvae, providing a potential nutrient source for the Streptomyces [ 37 ]. Therefore, the Streptomyces use different VOCs for eliciting trans-kingdom interactions and for influencing biological outcomes, demonstrating the importance of such molecules in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report has also shown that newly mated queens of Solenopsis invicta (red imported fire ant) are attracted by geosmin and 2-MIB to Streptomyces -rich locations for nesting, which have reduced levels of pathogenic fungi [ 36 ]. In addition, 2-MIB attracts Drosophila melanogaster (common fruit fly) for oviposition, where other Streptomyces specialized metabolites, such as cosmomycin D and avermectin, kill the larvae, providing a potential nutrient source for the Streptomyces [ 37 ]. Therefore, the Streptomyces use different VOCs for eliciting trans-kingdom interactions and for influencing biological outcomes, demonstrating the importance of such molecules in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…First, interspecies mutualism can help the dispersal of microorganisms ( 15 ). Actinobacteria have been reported to release geosmin and 2-methylisoborneol, terpenoid substances which can attract soil-dwelling arthropods (e.g., springtails) as food sources and/or defensive symbionts ( 16 ) to help them disperse in fecal pellets and/or attach to bodies when arthropods move around ( 17 ). Such a dispersal mechanism could partly explain the dominance of Actinobacteria in ancient tombs and/or caves.…”
mentioning
confidence: 99%
“…The exact reason for the production of plant-associated metabolites by Streptomyces is currently not clear, but since these bacteria inhabit the rhizosphere ( 125 ), it is possible that such metabolites (including VOCs) have roles in eliciting interactions with plants and other organisms in the environment ( 2 ). It was recently reported that certain Streptomyces strains produce VOCs to attract arthropods for the purposes of spore dispersal or to cause their killing for nutrient acquisition ( 23 , 24 ). In addition, some insects sense specific bacterial VOCs and are repelled by them as a possible mechanism of avoidance ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…The VOCs geosmin and 2-methylisoborneol, which are responsible for the characteristic earthy odor of soil are also produced by Streptomyces and are thought to be involved in attracting invertebrates such as arthropods so that Streptomyces spores can adhere to them for dispersal ( 23 ). It has also been reported that fruit flies are attracted by low levels of 2-methylisoborneol produced by certain Streptomyces species, which then use another specialized metabolite to kill and utilize the flies, possibly for nutritional purposes ( 24 ). Concomitantly, some insects avoid geosmin and higher levels of 2-methylisoborneol, which possibly signal danger due to the presence of Streptomyces in the vicinity ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%